2014
DOI: 10.1097/aap.0000000000000126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Task-Specific Checklist and Global Rating Scale for Ultrasound-Guided Regional Anesthesia

Abstract: Background and ObjectivesChecklists and global rating scales (GRSs) are used for assessment of anesthesia procedural skills. The purpose of this study was to evaluate the reliability and validity of a recently proposed assessment tool comprising a checklist and GRS specific for ultrasound-guided regional anesthesia.MethodsIn this prospective, fully crossed study, we videotaped 30 single-target nerve block procedures performed by anesthesia trainees. Following pilot assessment and observer training, videos were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…As there is no gold standard for defining expertise in regional anaesthesia, we used a surrogate measure of the trainee's volume of practice at the time of video recording to quantify experience. In the clinical validation study of an UGRA-specific checklist by Wong et al [17], trainees were divided into inexperienced and experienced practitioners based on a cut-off of 30 previous blocks at the time of video recording. Using this same definition, this study showed that the RAPS checklist, GRS and overall pass or fail items were equally able to discriminate trainees based on experience.…”
Section: Discussionmentioning
confidence: 99%
“…As there is no gold standard for defining expertise in regional anaesthesia, we used a surrogate measure of the trainee's volume of practice at the time of video recording to quantify experience. In the clinical validation study of an UGRA-specific checklist by Wong et al [17], trainees were divided into inexperienced and experienced practitioners based on a cut-off of 30 previous blocks at the time of video recording. Using this same definition, this study showed that the RAPS checklist, GRS and overall pass or fail items were equally able to discriminate trainees based on experience.…”
Section: Discussionmentioning
confidence: 99%
“…Small patient sample sizes and lack of practitioner randomization with respect to level of training and regional anesthesia technical expertise as drawbacks to global evaluation of procedural proficiency has been reported in prior assessments of these skills [8,25]. Small numbers of procedural observations on large numbers of trainees have been reported as a source of methodological bias [26]. Reduction of the bias effects of small sample size, nonrandom selection of practitioner and nerve block technique, and trainee cohort variability in training has been attempted by the employment of multiple standard observers and protocols [27].…”
Section: Preop -Preoperative Intraop -Intraoperative Pacu -Immediatmentioning
confidence: 99%
“…2-5 Out of more than 30 elements in 1 recent assessment tool, only 1 element focuses on recognizing anatomic structures, with 2 reserved for recognizing proper needle and injectate location. 3,4 The remainder of the instrument centers around procedural steps like patient positioning, probe selection, needle alignment, and injection technique. Mastery of UGRA requires reliable performance of all these steps and moreincluding adherence to sterile technique, anatomic knowledge, 2-hand 3-dimensional coordination, patient communication, and monitoring vigilance.…”
mentioning
confidence: 99%